THE ANALYSIS OF STUDENT’S WRITING BEFORE AND AFTER THE IMPLEMENTATION OF READ-TO-WRITE APPROACH - Rosmawan, Hana (Fakultas Ilmu Budaya, Universitas Mulawarman, 2016)
The focus of this article is on the analysis of student’s writing before and after the implementation of Read-to-Write Approach. Read-to-write approach is one of strategies of how to write by reading the articles what other writers have written. This study aimed to find out how the students’ writing skill can be improved through the implementation of read-to-write approach. This research used the instruments of writing tests including pre-test and post-test. The finding showed that students’ writing skill could be improved through the implementation of read-to-write approach during one cycle classroom action research which consisted of four meetings. Actually, this article searched deeply to find out how the differences between the writing results of the student after and before the implementation of read-to-write approach. The analysis was conducted by using analytic scoring rubric. The results of the analysis showed improvement on each aspect of writing.Keywords: read-to-write approach, reading and writing skill, holistic scoring rubric, analytic scoring rubric